(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The objective of this paper is to reflect on the regulatory status of National Law No. 25,673 Sexual Health and Responsible Procreation (SSyPR) in Tucumán, a province in northern Argentina. This regulation was enacted in 2002 but after 20 years of sanction, Tucumán still has not pronounced adherence to it. We intend to reflect on the effects and social meanings that this normative situation has in the region. For this, we carry out an interpretive work that relates the attempts to implement the regulations with social and cultural characteristics of the province reflected in events that the local press recorded. Likewise, we conducted interviews with key informants, experts on the subject and leaders responsible for the execution of said law at the local level. The analysis model is based on the intersectional perspective and gender studies. The conclusions show that the provincial non-adherence to the national regulations is a symbolic barrier that limits the full implementation of the law. In addition, it entails situations of institutional violence and violation of sexual and reproductive rights of the population in general, but especially of women, girls and adolescents.